2016
DOI: 10.1002/prca.201500136
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics study reveals that the dysregulation of focal adhesion and ribosome contribute to early pregnancy loss

Abstract: PurposeEarly pregnancy loss (EPL) affects 50–70% pregnant women in first trimester. The precise molecular mechanisms underlying EPL are far from being fully understood. Therefore, we aim to identify the molecular signaling pathways relating to EPL.Experimental designWe performed proteomics and bioinformatics analysis of the placental villi in women who have undergone EPL and in normal pregnant women. The proteomics data were validated by Western blot analysis.ResultsWe identified a total of 5952 proteins in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
1
10
1
Order By: Relevance
“…Further bioinformatics analysis indicated that these differentially expressed proteins participated in a variety of signaling pathways, including the focal adhesion pathway and ribosome pathway. [33] These identified proteins, especially those with known roles in apoptosis and oxidative stress, may be novel predictive markers for MA.…”
Section: Discussionmentioning
confidence: 99%
“…Further bioinformatics analysis indicated that these differentially expressed proteins participated in a variety of signaling pathways, including the focal adhesion pathway and ribosome pathway. [33] These identified proteins, especially those with known roles in apoptosis and oxidative stress, may be novel predictive markers for MA.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 13 used sliver-stained 2-DE profiling and found 18 differentially expressed proteins, of which 13 were downregulated and 5 were upregulated. Similarly, Xin et al 14 differentially using gel-free TMT labeling. Hence, differential protein expression studies in the EM patients have been of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 13 used sliver-stained 2-DE profiling and found 18 differentially expressed proteins, of which 13 were downregulated and 5 were upregulated. Similarly, Xin et al 14 used tandem mass tag (TMT) labeling-based proteomics and identified 5952 differentially expressed proteins in placental villi of EM patients compared to controls. Ni et al 15 identified 3423 proteins and reported 51 proteins expressed differentially using gel-free TMT labeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 6 studies [21][22][23][24][25] only one study identified one Hsp10 peptide [26], although 100-800 other proteins were identified in these studies. Hsp10 is not intrinsically difficult to detect by mass spectroscopy [27,28]. Using an antibodycapture ELISA (detection limit 0.5 ng/ml) [29], Cpn10 levels were mostly at or below the detection limit, with no indication that levels in mouse pregnancy were significantly elevated ( Figure 2).…”
mentioning
confidence: 99%